Hubungan Ilmu Ushul Fiqh Dengan Fiqh Serta Tujuan Mempelajarinya - Nursaman (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2022)
The position of ushul fiqh as the basis of Islamic fiqh, meaning that ushul fiqh is the sources/dalils and how to show these propositions to sharia law in general. Without a discussion of ushul fiqh, Fiqh cannot be created because the basis of ushul fiqh must be understood first, so that ushul fiqh is knowledge of various rules and language which are a means of deriving sharia laws regarding human actions regarding their detailed arguments. The science of ushul fiqh and the science of fiqh are two things that cannot be separated. The science of ushul fiqh can be likened to a factory that processes data and produces a product, namely the science of fiqh.